Socioeconomic variation in the relationship between obesity and life expectancy - Jonas Minet Kinge; Stephen Morris (Statistics Norway, Research Department, 2012)
We investigate the relationship between obesity and life expectancy, and whether or not this relationship varies by socioeconomic status (SES). The underlying model is based on the "Pathways to health" framework in which SES affects health by modifying the relationship between lifestyles and health. We use data from the British Health and Lifestyle Survey (1984-1985) and the longitudinal follow-up in June 2009, and run parametric Gompertz survival models to investigate the association between obesity and life expectancy, also accounting for interactions between obesity and both age and SES. Generally we find that obesity is negatively associated with survival, and that SES is positively associated with survival, in both men and women. There is no evidence of interactions between obesity and SES in predicting survival in men, but these interactions are present in women. Obesity is associated with lower survival in women except for older women in higher SES groups, who have a longer predicted survival than women of normal weight in this group.
Keywords: I14; I18; I19; 330; obesity; life expectancy; socioeconomic status; survival analysis